Reflection of Irony in O. Henry's The Gift of Magi and Firat Cewerî's Bîsîklêt Stories - Çeliktaş, Sami (Artuklu Kurdology, 2025)
In this study, an analysis was conducted of the stories of the American short-story writer O. Henry and the Kurdish short-story and novel writer Firat Cewerî, The Gift of Magi and Bîsîklêt, in the context of irony. Such an approach is well-suited to the field of comparative literature. This study examined the literary data that could be provided by analysing two writers and their works, who have different literary, historical and social backgrounds, around a common theme of examination. An analysis of the ironic discourses in the two stories, both of which featured similar subjects and themes, was conducted within the framework of the main types of verbal irony, including situational and dramatic irony, with the aim of explaining how irony functioned in the discourse of each story and how it was connected to the fundamental elements of the narrative. Following a thorough analysis, it was determined that both writers employed the literary device of irony to shed light on the social and personal challenges faced by their characters. Irony functioned as both a narrative tool and a key plot element, allowing for the expression of deep human emotions and experiences. In addition, it was determined that while the use of irony was identified as a central feature of O. Henry's narrative structure, its employment by Firat Cewerî was found to be limited, and implicit rather than explicit, allowing readers to interpret it through the medium of their own experiences and perspectives.